ضمانات حصول المتَّهم على المحاكمة العادلة وتطبيقاتها دراسة ميدانية تحليلية على ضوء القانون الفلسطيني والشَّريعة الإسلاميّة - رمضان محمد عبد الله عوض
The study aims to identify the principles of fair trial in Islamic law; to identify the extent to which the Palestinian law is committed to provide guarantees for the accused in obtaining a fair trial compared to Islamic law; to explain the adequacy of the available guarantees in achieving a fair trial for the accused in the Palestinian Penal Procedure Law compared to Islamic law; and to identify the extent to which the employees of the Palestinian police force and judiciary adhere to the provisions of the law to ensure the right of the accused to a fair trial. This study sought to determine the guarantees of the accused in the trial stage. The study used the comparative approach and the analytical descriptive method that integrated quantitative and qualitative. It is the appropriate method for studies that employ fieldwork, such as an interview or a questionnaire. The study concluded that the level of application of the guarantees from the point of view of the accused was moderate, as it was found that there is delay experienced by the accused in obtaining the decision for his conviction or release. This delay is caused by the court from the point of view of the accused. It was also found that there was failure from the Public Prosecution to examine witnesses without pressure in accordance with the law; failure in the judge’s assurance that the confession was not extracted from the accused by force and with regard to the judge’s assurance that the accused was not subjected to torture before the trial; as well as with regard to the right of the accused not to postpone the trial more than once. The results of this study, according to a survey of Palestinian lawyers in Palestinian courts, showed that the percentage of fairness achievement was moderate. They have some objections to achieving fairness, represented in the fact that the judge does not put the interest of the accused first in all procedures, and the judge does not usually stand by the accused until proven otherwise. The results showed that the lawyers’ survey shows that the achievement of fairness in the Islamic system in the past is better than the system in the courts of today in terms of achieving fairness and ensuring that the accused obtains fairness during the trial. They also see that putting the accused in a cage is a violation of his right, a procedure that was not used in the Islamic judiciary in the past. Likewise, they do not believe that the principles of trial in courts today are derived from Islamic law. The results of the study showed that the Public Prosecution sees that fairness is achieved by the court, and that the Palestinian judicial system is impartial and achieves a high level of fairness in dealing with the accused. They believe that the judicial system is impartial and takes into account all the rights of the accused and seeks to implement them. The results also showed that the judges see fairness and legal integrity in dealing with the accused, guaranteeing his rights in all stages of the trial until the verdict is issued, and that there are some mistakes that must be addressed.